Tumour‐suppressive microRNA‐29s directly regulate LOXL2 expression and inhibit cancer cell migration and invasion in renal cell carcinoma. Issue 16 (19th June 2015) - Nishikawa, Rika; Chiyomaru, Takeshi; Enokida, Hideki; Inoguchi, Satoru; Ishihara, Tomoaki; Matsushita, Ryosuke; Goto, Yusuke; Fukumoto, Ichiro; Nakagawa, Masayuki; Seki, Naohiko
Abstract : Here, we found that members of the microRNA‐29 family ( miR‐29a/b/c ; " miR‐29s ") were significantly reduced in clear cell renal cell carcinoma (ccRCC) tissues, suggesting that they functioned as tumour suppressors. Restoration of all mature members of the miR‐29 family inhibited cancer cell proliferation, migration and invasion. LOXL2 was a direct target gene of miR‐29s, as shown by genome‐wide gene expression analysis and luciferase reporter assay. Overexpressed LOXL2 was confirmed in ccRCC clinical specimens, and silencing of LOXL2 inhibited cancer cell migration and invasion in ccRCC cell lines. Our data demonstrated that the miR‐29s‐LOXL2 axis contributed to cancer cell migration and invasion in ccRCC. Abstract : All members of the miR‐29 family were downregulated in ccRCC tissues compared with normal kidney tissues. Restoration of miR‐29s inhibited cancer cell proliferation, migration and invasion in ccRCC cell lines. LOXL2 was a direct target of miR‐29s and was upregulated in ccRCC tissues. LOXL2 and miR‐29 expression were negatively correlated in clinical specimens. Silencing of LOXL2 inhibited cancer cell migration and invasion in ccRCC cell lines.